Faktor Pengaruh Iklim Keselamatan Kerja dalam proyek Konstruksi: Studi Literatur - Diah Listyaningsih; Feri Harianto; Rahma Saraswati (Jurnal Teknik Sipil, 2020)
Accidents in construction project often occur, especially in the construction world. Safety climate plays an important role in the success of a project. By using a literature study, this article aims to find out what factors affect climate. This study uses 14 journals and consists of 17 articles that focus on the climate of work safety. The results showed that 13 factors were generated which were categorized into physical and non-physical. Physical factors that influence are physical fatigues, low adaptability, motor skills, leadership management, systematic work preparation, safety behaviour and injuries. Meanwhile, non-physical consisted of 5 factors: organizational climate, emotional stress, psychological conflict, personality, intelligence and motivation, psychosocial conditions. For further research, factor analysis will be carried out regarding the factors that have been found by surveying construction workers in Indonesia. The association of these factors with the safety climate can also be found.